A decline in functional status while awaiting liver transplantation is predictive of increased post-transplantation mortality. Issue 6 (June 2022) - Bezinover, Dmitri; Geyer, Nathaniel R.; Dahmus, Jessica; Chinchilli, Vernon M.; Stine, Jonathan G.
Abstract: Background: Functional status (FS) is dynamic and changes over time. We examined how changes in FS while awaiting liver transplantation influence post-transplant outcomes. Methods: Data on adult liver transplants performed in the United States during the MELD era were obtained through September 2020. Patient and graft survival were compared between groups with no change or improved FS, and those with worsening FS. Results: Of the 90, 210 transplant recipients included in the analysis, 39, 193 (43%) had worsening FS, which was associated with longer waiting-list time (187 vs. 329 days, p < 0.001) and worse patient survival after liver transplant (1858 vs. 1727 days, p < 0.001). A consistent and dose-dependent relationship was observed for each 10-point decrease in Karnofsky Performance Score and post-transplant survival. Multivariable regression analysis confirmed that a decline in FS was associated with worse patient survival (HR 1.15, p < 0.001). Similar findings were observed for graft survival. Conclusion: A decline in FS on the waiting-list is associated with significantly greater post-liver transplant mortality in recipients. These results should be taken into consideration when allocating organs and determining transplant candidacy. Strategies to optimize FS prior to transplantation should be prioritized as even subtle decreases in FS are associated with inferior post-transplantation outcomes.